The High Risk of Bivalve Farming in Coastal Areas With Heavy Metal Pollution and Antibiotic-Resistant Bacteria: A Chilean Perspective - Pavón, Alequis; Riquelme, Diego; Jaña, Víctor; Iribarren, Cristian; Manzano, Camila; Lopez-Joven, Carmen; Reyes-Cerpa, Sebastián; Navarrete, Paola; Pavez, Leonardo; García, Katherine (Frontiers in Cellular and Infection Microbiology, 2022)
Anthropogenic pollution has a huge impact on the water quality of marine ecosystems. Heavy metals and antibiotics are anthropogenic stressors that have a major effect on the health of the marine organisms. Although heavy metals are also associate with volcanic eruptions, wind erosion or evaporation, most of them come from industrial and urban waste. Such contamination, coupled to the use and subsequent misuse of antimicrobials in aquatic environments, is an important stress factor capable of affecting the marine communities in the ecosystem. Bivalves are important ecological components of the oceanic environments and can bioaccumulate pollutants during their feeding through water filtration, acting as environmental sentinels. However, heavy metals and antibiotics pollution can affect several of their physiologic and immunological processes, including their microbiome. In fact, heavy metals and antibiotics have the potential to select resistance genes in bacteria, including those that are part of the microbiota of bivalves, such as Vibrio spp. Worryingly, antibiotic-resistant phenotypes have been shown to be more tolerant to heavy metals, and vice versa, which probably occurs through co- and cross-resistance pathways. In this regard, a crucial role of heavy metal resistance genes in the spread of mobile element-mediated antibiotic resistance has been suggested. Thus, it might be expected that antibiotic resistance of Vibrio spp. associated with bivalves would be higher in contaminated environments. In this review, we focused on co-occurrence of heavy metal and antibiotic resistance in Vibrio spp. In addition, we explore the Chilean situation with respect to the contaminants described above, focusing on the main bivalves-producing region for human consumption, considering bivalves as potential vehicles of antibiotic resistance genes to humans through the ingestion of contaminated seafood.